2009
DOI: 10.21608/mjfmct.2009.52969
|View full text |Cite
|
Sign up to set email alerts
|

Determination Of Subpubic Angle In Egyptian Population

Abstract: Abd-El-hameed et al ... differences, both osteometric and morphological, between the sexes of a particular racial phenotype and population (Steyn and Iscan, 1998). Original attempts to determine the sex were made for those bones of the pelvis and the skull with the idea that they are the best indicators of the gender. It is thought that, to some extent, the shape of the pelvis may correlate with that of the INTRODUCTlON Sex determination of unknown skeletal material is one of the most vital determinations made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Though our study findings cannot be generalized for our population due to the smaller sample size, this widely accepted simple rule of 90° SPA for sex determination may not still be applicable in our population as mean SPA in the male in our study is way more than the cut-off value. 4,5,6,7,8,9 SPA in our study is comparable to the SPA in the study done by Akhlaghi et al (140.0° ± 14.3° in male and 101.0° ± 13.3° in female), but wider than the SPA in above mentioned other similar studies. 8 The differences may be due to the different ethnic groups studied.…”
Section: Discussionsupporting
confidence: 88%
“…Though our study findings cannot be generalized for our population due to the smaller sample size, this widely accepted simple rule of 90° SPA for sex determination may not still be applicable in our population as mean SPA in the male in our study is way more than the cut-off value. 4,5,6,7,8,9 SPA in our study is comparable to the SPA in the study done by Akhlaghi et al (140.0° ± 14.3° in male and 101.0° ± 13.3° in female), but wider than the SPA in above mentioned other similar studies. 8 The differences may be due to the different ethnic groups studied.…”
Section: Discussionsupporting
confidence: 88%
“…While there might be some discrepancy due to the study's design focusing on the adult female population in southwestern Iran, both studies yielded nearly identical measurements (14). This finding closely aligns with previously reported subpubic angle measurements (21)(22)(23). The wide variation in pubic arch angles observed in our study could have implications for sling placement and tensioning.…”
Section: Discussionsupporting
confidence: 86%
“…Khodeary, et al and Kayastha P, et al also found higher SPA (102.31±12.50° and 104.72±10.47° respectively) than the most accepted cut-off value in male. 15,16 Mohad Ali SH, et al discovered SPA in female was 87.4±6.5° using a threedimensional computed tomography model of the pelvis, which is less than the widely accepted cut-off value in female. 3 Hence, the sex determination using the cut-off value of 90° is not always accurate and may not be applicable to all the population.…”
Section: Iscussionmentioning
confidence: 96%
“…Similar findings were observed in several other studies. 1,15,16 The subpubic concavity does not fully develop in females until they reach the age of 20 years. 8 As a result, there is no sexual dimorphism in the preadolescent pelvis.…”
Section: Iscussionmentioning
confidence: 99%